Floqita / Nur Adlina Muhd Azmi ...[et al.] - Azmi, Nur Adlina; Mohd Kharul, Noor Haniah; Mohd Ilham, Izzatul Wajeeha; Ghazali @ A. Shukor, Nabihah (2023)
Floqita Boutique is a new boutique that was founded by five people through partnership. The business is planned to be located at Nanyang Place @ Austin Heights, Mount Austin Jalan Austin Heights 7, Johor Bahru. This is because the area is strategic for build up the business since the place is near to living residential which will make people come to boutique frequently. Other than that, at the area, there are few rivals, ensuring that the consumer chooses our boutique. This business will be commencing on the 1st of January 2023. The vision of this boutique is wants “To aim that the brand is well-known in Malaysia, then throughout Southeast Asia, Asia, and ultimately the entire world” and the mission is “To ensure that all women can feel the comfortability in their own skin when wear our clothes. By never compromising our quality in clothes, FLOQITA have attracted customers and will continue to retain the customer interest in our product. There is five position under the administration personnel, and they are General Manager, Administration Manager, Marketing Manager, Operation Manager, and Financial Manager. Everyone has their own task and responsibilities. FLOQITA business it has their own office and also a shop for customer to buy FLOQITA products. FLOQITA shop and the office it is located at the same location at Nanyang Place @ Austin Heights, Mount Austin Jalan Austin Heights 7, Johor Bahru. It is a two-floor building where the office is at upstairs and the shop is below. Floqita opens the business at 10a.m. until 10p.m. from Monday to Friday and 10 a.m. until 11p.m. from Saturday to Sunday. Floqita offers a wide range of goods, including tops, pants, skirts, hijabs, sportswear, and even accessories. The product is unique because it is odorless, ironless, breathable, and has permanent antimicrobial. Poly cotton, twill knit, and knitted poly are some of the materials used. A Business Modal Canvas (BMC) is also used by us to better comprehend the planning. A strategic management tool for creating new or current business models is the company model canvas. Last but not least, it gives us great joy to serve as a model for other people looking to launch a career in the fashion industry, particularly when it comes to creating unusual clothing that will astound many people.